Pengaruh Harga, Promosi dan Kelengkapan Produk Terhadap Loyalitas Konsumen Melalui Kepuasan Pelanggan - Rita Rita; Kaleb Finney Irwan (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to analyze the influence of price, promotion, and product completeness on consumer loyalty through customer satisfaction at ACC Andi stationery stores. The research method uses a quantitative approach with explanatory research techniques. Data was collected through a questionnaire from 230 respondents selected by purposive sampling technique. Data analysis uses the Structural Equation Model (SEM) with SmartPLS. The results of the study show that price, promotion, and completeness of products have a positive and significant effect on customer satisfaction and consumer loyalty, both directly and indirectly through customer satisfaction. Customer satisfaction has also been proven to have a positive and significant effect on consumer loyalty. These findings indicate the importance of the right pricing strategy, effective promotion, and adequate product completeness in increasing consumer satisfaction and loyalty. The implications of this research provide insight for stationery store management in developing effective marketing strategies to maintain and increase the loyal customer base during increasingly fierce industry competition